Analisis Pesan Dakwah Ustadz Muhammad Nuzul Dzikri Melalui Media YouTube - Rofiqotul Fidha; Rofi’ah Rofi’ah; Noneng Siti Rosidah (Universitas Pahlawan Tuanku Tambusai, 2024)
Da'wah on the aspects of Islam, namely creed, morals, and sharia, has an important role in strengthening the beliefs, understanding, and religiosity of Muslims. In today's digital era, online platforms such as YouTube are a significant means of disseminating da'wah messages to a wide audience. This study aims to analyze Ustadz Muhammad Nuzul Dzikri's da'wah messages through YouTube media. The research method used is a case study with a qualitative approach. Data is collected through observation of the da'wah content delivered through the YouTube channel, as well as documentation to find out and understand the content of the da'wah. The results of this study are expected to provide an overview of the extent to which da'wah through YouTube can be effective in spreading understanding of creed, morals and shari'ah to the wider community.